Experiences of criminal justice : perspectives from Wales on a system in crisis - Newman, Daniel (Law teacher); Dehaghani, Roxanna (Bristol : Bristol University Press, 2022)
Austerity continues to impact the criminal justice process in England and Wales: police numbers are down, the Crown Prosecution Service is in disarray, legal aid has been reduced, courts are closing and magistrates are leaving. Research into the criminal process usually focuses on England, however this book offers a rare insight into South Wales. Drawing on first-hand accounts of lawyers, police, and suspects, the convicted and their families, it uncovers how these affected individuals navigate the challenges caused by austerity, what has changed, and what can be done to improve the system. This book is a reliable and evocative account of the reality of criminal justice in Wales.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on October 19, 2022).
Keywords: Criminal justice, Administration of -- Wales; Legal services -- Wales; Criminal justice, Administration of -- Social aspects -- Wales; True Crime; Social services & welfare, criminology